Comprehensive disease control (CDC): what does achieving CDC mean for patients with rheumatoid arthritis?. Issue 12 (19th August 2014) - Emery, Paul; Kavanaugh, Arthur; Bao, Yanjun; Ganguli, Arijit; Mulani, Parvez
Abstract : Background: This study assessed the impact of simultaneous achievement of clinical, functional and structural efficacy, herein referred to as comprehensive disease control (CDC), on short-term and long-term work-related outcomes, health-related quality of life (HRQoL), pain and fatigue. Methods: Data were pooled from three randomised trials of adalimumab plus methotrexate for treatment of early-stage or late-stage rheumatoid arthritis (RA). CDC was defined as 28-joint Disease Activity Score using C reactive protein <2.6, Health Assessment Questionnaire <0.5 and change from baseline in modified Total Sharp Score ≤0.5. Changes in scores at weeks 26 and 52 for work-related outcomes, Short Form 36 (SF-36) physical (PCS) and mental component scores (MCS), a Visual Analogue Scale measuring pain (VAS-Pain) and Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) were compared between patient groups defined by achievement of CDC at week 26 using linear regression with adjustment for baseline scores. Results: Patients with RA who achieved CDC at week 26 (n=200) had significantly greater improvements in VAS-Pain (46.9 vs 26.9; p<0.0001), FACIT-F (13.3 vs 7.5; p<0.0001), SF-36 PCS (19.7 vs 8.9; p<0.0001) and SF-36 MCS (8.1 vs 5.0; p=0.0004) than those who did not (n=1267). Results were consistent at week 52 and among methotrexate-naive patients with early RA, methotrexate-experienced patients with late-stage RA and patients with inadequate response to methotrexate. Conclusions: Patients with RA who achieved CDC at week 26 had improved short-term and long-term HRQoL, pain, fatigue and work-related outcomes compared with patients who do not. These results demonstrate that the joint achievement of all CDC components provides meaningful benefits to patients. Trial registration numbers: DE019: NCT00195702, PREMIER: NCT00195702, OPTIMA: NCT00195702 .